Factors affecting commencement and cessation of betel quid chewing behaviour in Malaysian adults. - Ghani, W.M.; Razak, I.A.; Yang, Y.H.; Talib, N.A.; Ikeda, N.; Axell, T.; Gupta, P.C.; Handa, Y.; Abdullah, N.; Zain, R.B. (1990)
BACKGROUND: Betel quid chewing is a common habit widely practiced in Southern Asian populations. However, variations are seen in the content of a betel quid across the different countries. Factors associated with commencement and cessation of this habit has been numerously studied. Unfortunately, data on Malaysian population is non-existent. This study aims to determine the factors associated with the inception and also cessation of betel quid chewing behaviour among Malaysian adults.